Automatic segmentation of the fetal cerebellum on ultrasound volumes, using a 3D statistical shape model. - Gutiérrez-Becker, Benjamín; Arámbula Cosío, Fernando; Guzmán Huerta, Mario E; Benavides-Serralde, Jesús Andrés; Camargo-Marín, Lisbeth; Medina Bañuelos, Verónica (Medical & Biological Engineering & Computing, 2013)
Previous work has shown that the segmentation of anatomical structures on 3D ultrasound data sets provides an important tool for the assessment of the fetal health. In this work, we present an algorithm based on a 3D statistical shape model to segment the fetal cerebellum on 3D ultrasound volumes. This model is adjusted using an ad hoc objective function which is in turn optimized using the Nelder-Mead simplex algorithm. Our algorithm was tested on ultrasound volumes of the fetal brain taken from 20 pregnant women, between 18 and 24 gestational weeks. An intraclass correlation coefficient of 0.8528 and a mean Dice coefficient of 0.8 between cerebellar volumes measured using manual techniques and the volumes calculated using our algorithm were obtained. As far as we know, this is the first effort to automatically segment fetal intracranial structures on 3D ultrasound data.